2010
DOI: 10.3758/s13415-010-0008-8
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery effectiveness for mirror reversed movements

Abstract: Physical practice is known to enhance motor adaptation skills, which refer to the individual ability to compensate for environmental changes. So far, it is still unknown whether a similar effect can be observed following motor imagery (MI). Thirty-nine participants were tested during a joystick tracking task under both normal and mirror conditions (i.e., the inductive direction of the joystick was reversed), before and after a physical practice or MI training phase. Eye movements and electromyographic activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…Based on these findings, it is assumed that activation of (motor) representations is also responsible for behavioral adaptations after non-physical training. For instance, motor imagery was shown to improve the acquisition of motor sequence learning paradigms (e.g., Debarnot et al, 2011a ), tracking tasks (Debarnot et al, 2011b ), strength exercises (e.g., studies summarized in table 1 in Reiser et al, 2011 ), and a variety of sport activities (e.g., Guillot et al, 2013 ). Similarly, observational learning was reported to promote acquisition of movement sequences (van der Helden et al, 2010 ), adaptations to force fields (Mattar and Gribble, 2005 ), the learning of guitar chords (Higuchi et al, 2012 ), increasing strength (Porro et al, 2007 ) and an improvement in sports performance (e.g., Lawrence et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it is assumed that activation of (motor) representations is also responsible for behavioral adaptations after non-physical training. For instance, motor imagery was shown to improve the acquisition of motor sequence learning paradigms (e.g., Debarnot et al, 2011a ), tracking tasks (Debarnot et al, 2011b ), strength exercises (e.g., studies summarized in table 1 in Reiser et al, 2011 ), and a variety of sport activities (e.g., Guillot et al, 2013 ). Similarly, observational learning was reported to promote acquisition of movement sequences (van der Helden et al, 2010 ), adaptations to force fields (Mattar and Gribble, 2005 ), the learning of guitar chords (Higuchi et al, 2012 ), increasing strength (Porro et al, 2007 ) and an improvement in sports performance (e.g., Lawrence et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In attempts to elucidate the role of eye movements during movement imagery, some researchers have employed chronometry paradigms and included conditions in which eye movements are fixed or free (Gueugneau et al, 2008; Debarnot et al, 2011). Using a joystick tracking task, under normal and mirror conditions, Debarnot et al (2011) reported that performance accuracy and temporal similarity between physical execution and movement imagery is maintained in the normal condition for eyes-free and eyes-fixed, which suggests that eye movements perform no functional role.…”
Section: Congruency Of Gaze Metricsmentioning
confidence: 99%
“…Using a joystick tracking task, under normal and mirror conditions, Debarnot et al (2011) reported that performance accuracy and temporal similarity between physical execution and movement imagery is maintained in the normal condition for eyes-free and eyes-fixed, which suggests that eye movements perform no functional role. However, in the mirror condition the temporal congruence between action execution and movement imagery was maintained only in the eyes-free condition.…”
Section: Congruency Of Gaze Metricsmentioning
confidence: 99%
“…Dans ces deux conditions, par exemple, la vision anticipe la position de la main pour faciliter la saisie d'un objet. Cependant, ces résultats n'ont pasété systématiquement confirmés (e.g., Debarnot, Valenza, Champely, Scilingo, De Rossi, & Guillot, 2011 ;Gueugneau, Crognier, & Papaxanthis, 2008), même si plusieursétudes valident l'hypothèse de l'identité des mouvements oculaires lors de l'exécution réelle et de sa représentation mentale (Heremans et al, 2011(Heremans et al, , 2012 (McCorry, 2007). Les effecteurs sont les organes internes, comme le coeur, mais aussi la musculature lisse, les glandes exo-et endocrines.…”
Section: Mouvements Oculairesunclassified